Multi-scale characteristics of an extreme rain event in Shandong Province, produced by Typhoon Lekima (2019) - Gao, Yue; Zhang, Yi; Lei, Lili; Tang, Jie (Frontiers in Earth Science, 2023)
Super typhoon Lekima (2019) is the 5th strongest typhoon to make landfall in mainland China since 1949. After its landfall, typhoon Lekima moved northward along the coastline, resulting in an extreme rain event in Shandong Province that makes the largest precipitation within the available meteorological records. A WRF model simulation that well produces the track and intensity of typhoon Lekima and the spatio-temporal evolution of the rainfall is used to analyze the multi-scale characteristics of the extreme rain event. Different from the typhoon precipitation occurred at low latitudes, the extreme rain event occurred in midlatitudes were influenced by the interactions of midlatitude synoptic systems and typhoon circulation, especially with five mesoscale rainbands. The midlatitude synoptic systems, mainly including the upper-tropospheric jet, the Western North Pacific Subtropical High, the mid-latitude trough, the low-level jets and typhoon Krosa (2019), allow typhoon Lekima to maintain its intensity after landfall and provide favorable kinematic, thermodynamic and moisture conditions for the heavy rainfall in Shandong. Based on the evolution of the mesoscale rainbands, the extreme rain event can be divided into three stages. The first stage can be classified as a distant rainfall, which was affected by two convective rainbands associated with boundary layer processes. The second stage had the largest precipitation, featured the formation of a frontal zone in Shandong interacting with typhoon Lekima. The third stage had weakened rainfall and was directly influenced by the spiral rainband of typhoon Lekima.